IMAM NAWAWI'S THOUGHTS ABOUT TEACHER PERSONALITY COMPETENCE AND ITS RELEVANCE TO NATIONAL EDUCATIONAL STANDARDS - Yudistiro, Toro; Rohimah, Siti (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
The education system expects teachers to be more competent in their work as educators, meaning that teachers who are proficient in their work are competent and professional teachers. The purpose of this study is to find the concept of educator personality from al-Imām an-Nawawī's thoughts in his book At-Tibyān Fī 'Ādāb Hamalati Al-Qur'ān and also its relevance to the National Education Standards that have been set by the Education Office. The type of research that researchers use is qualitative research with a library and field research approach. The primary data source is from the book At-Tibyān written by Al-Imām Al-Nawawi. From the analysis that has been carried out, it is found that the concept of educator personality from Imam Nawawi's thoughts, namely: (1) Educators must carry out their responsibilities sincerely with the sole intention of expecting the pleasure of Allah SWT. (2) Educators do not intend to obtain worldly pleasures. (3) Educators must always be careful and thorough. (4) Educators should adorn themselves with commendable qualities and good morals. (5) Students must be treated well by educators. (6) Educators should advise their students. (7) Educators must be gentle and humble, be gentle and humble. (8) Students must be taught to behave in a way that is approved by Allah SWT by their teacher from ti me to time. (9) If there are many students, the teacher should give priority to the first student's turn and so on. (11) The teacher may not teach by coming to the student's place.